Enantioselective Synthesis of Amaryllidaceae Alkaloids (+)‐Vittatine, (+)‐epi‐Vittatine, and (+)‐Buphanisine. Issue 9 (20th June 2013) - Wei, Meng‐Xue; Wang, Cheng‐Tao; Du, Ji‐Yuan; Qu, Hu; Yin, Pei‐Rong; Bao, Xu; Ma, Xiao‐Yan; Zhao, Xian‐He; Zhang, Guo‐Biao; Fan, Chun‐An
<x xml:space="preserve">Abstract</x> Cat. on a hot tin roof: Enantioselective catalytic Michael addition of α‐cyanoketones to acrylates under bifunctional organocatalysis was used to construct the unique arylic all‐carbon quaternary stereocenter, which is synthetically crucial in the chemical synthesis of optically pure cis‐aryl hydroindole alkaloids. The protocol offers an asymmetric route to (+)‐vittatine, (+)‐epi‐vittatine, and (+)‐buphanisine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>